Chronic pulmonary sarcoidosis: relationship between lung lavage cell counts, chest radiograph, and results of standard lung function tests. Issue 7 (July 1985) - Lin, Y H; Haslam, P L; Turner-Warwick, M
Abstract : Thirty three consecutive untreated patients with pulmonary sarcoidosis, confirmed histologically or by Kveim test, were investigated to correlate cell counts in bronchoalveolar lavage fluid with clinical features, the chest radiograph, and results of lung function tests. A persistently abnormal radiograph had been observed for one year or more in 26 (79%) and for two years or more in 20 (61%), but only 24% had dyspnoea. Twenty (61%) of 33 patients showed an increased percentage of lymphocytes in bronchoalveolar lavage fluid, although only eight (24%) exceeded 28%. A moderate increase of neutrophils, up to 12%, was found in 14 (42%). Lymphocyte percentage counts were higher in the group of patients without evidence of radiographic contraction suggesting fibrosis, and this contrasted with higher percentage neutrophil counts in those with contraction. There was also a correlation between the percentages of neutrophils and increasing radiographic profusion scores (p less than 0.001), suggesting that neutrophils may reflect the severity of the parenchymal legions as well as fibrotic distortion, and an inverse correlation with vital capacity (p less than 0.001) and transfer factor (TLCO) (p less than 0.1 greater than 0.05). No significant correlation was found between the lymphocyte counts and radiographic profusion scores, vital capacity or TLCO; but it was noted that all eight patients with high lymphocyte counts (greater than 28%) had radiographic profusion scores less than 12. This study shows that, especially in sarcoidosis with more extensive radiographic shadows of long duration, bronchoalveolar lavage neutrophils may be important as well as lymphocytes in clinical assessment of "activity" of disease. These observations are important because they throw doubt on whether the lavage lymphocyte count alone can be used as an indicator of the need to start corticosteroid treatment.